Social reproduction within, outside and beyond capitalism: the role of prefigurative politics - Αδάμ Σοφία (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2025)
Social Reproduction Theory (SRT) has evolved into a rich and multifaceted theoretical corpus which enables both a deeper understanding of the current poly- and permacrisis of our times and the exploration of political strategies towards a post-capitalist future. This paper critically engages with SRT in order to offer further support on the analytical and political usefulness of the concept of social reproduction. More importantly, this paper addresses a missing link between SRT and prefigurative politics in the form of the Commons and Social Solidarity Economy. This missing link is crucial if we are to understand new struggles in the field of social reproduction and their positioning vis à vis overall capitalist societal reproduction. The main argument is that the Commons and Social Solidarity Economy approaches and practices have a role to play in social reproductive struggles in three interrelated ways: a) they articulate new and/or unmet social needs, b) they enact collective modes of provisioning, and c) they politicize alternative modes of collective provisioning.